2018
DOI: 10.3171/2016.11.jns161398
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular management of acute epidural hematomas: clinical experience with 80 cases

Abstract: OBJECTIVE Small acute epidural hematomas (EDHs) treated conservatively carry a nonmeasurable risk of late enlargement due to middle meningeal artery (MMA) lesions. Patients with EDHs need to stay hospitalized for several days, with neurological supervision and repeated CT scans. In this study, the authors analyzed the safety and efficacy of the embolization of the involved MMA and associated lesions. METHODS The study group consisted of 80 consecutive patients harboring small- to medium-sized EDHs treated by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
1
13
0
1
Order By: Relevance
“…To begin with, small EDHs are usually treated conservatively. Nevertheless, in some large samples of EDHs, it was found that the rate of re-expansion of hematoma after conservative treatment reached 5.5~65% ( 9 , 28 ). Sakai et al showed that 65% of small EDHs re-expansion in the first 24 h after trauma ( 29 ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…To begin with, small EDHs are usually treated conservatively. Nevertheless, in some large samples of EDHs, it was found that the rate of re-expansion of hematoma after conservative treatment reached 5.5~65% ( 9 , 28 ). Sakai et al showed that 65% of small EDHs re-expansion in the first 24 h after trauma ( 29 ).…”
Section: Discussionmentioning
confidence: 98%
“…A prospective study evaluating 22 patients who had small EDHs showed that 32% of the patients underwent surgical evacuation because of late enlargement ( 30 ). Furthermore, most studies of EDHs suggest that EDHs are related to tearing or damage to the MMA, seen as contrast agent extravasation, pseudoaneurysm, or arteriovenous fistula in DSA ( 28 , 31 ). However, the best treatment option for EDH in larger or occipital and non-middle meningeal arterial blood supply areas remains surgery ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce the economic burden, effect of added radiation, and risk of sudden clinical deterioration, the MMA can be embolized. 39 Angiography may reveal laceration, pseudoaneurysm, or an AVF. Enlarging EDH can occur up to 30 days after trauma.…”
Section: Intracranial Extra-axial Hematomasmentioning
confidence: 99%